Historical Communist Party Strength and Modern Party Loyalty. A Replication Study of Barceló (PNAS, 2021) - Edmund J. Malesky; Trung-Anh Nguyen (Journal of Comments and Replications in Economics (JCRE), 2024)
Does exposure to violence create more politically engaged citizens? In a PNAS paper, Barceló (2021) asks this provocative question and proposes an intricate and original socio-psychological theory to answer it. Barceló also employs a research design that seeks to account for reverse causality to address the fact that more engaged places may have been targeted. Unfortunately, even after a correction, his statistical analysis remains dogged by coding, historical, and contextual errors, which bias results and lead to misleading conclusions. When we account for these mistakes with simple and reasonable corrections, the main results no longer hold. Rather, we show that the true underlying explanation is more mundane: areas that were sources of pre-war communist insurgency strength were targeted for their activity during the conflict, and they remain more loyal to the regime today.
https://doi.org/10.15456/j1.2023285.1524615125
Keywords: P0; P2; P3; P5; N0; 330; Conflict; Civic engagement; Vietnam War; Historical legacies